Fabrication of microfluidic devices using MeV ion beam Programmable Proximity Aperture Lithography (PPAL) - S. Gorelick (2018)
MeV ion beam lithography is a direct writing technique capable of producing microfluidic patterns and lab-on-chip devices with straight walls in thick resist films. In this technique a small beam spot of MeV ions is scanned over the resist surface to generate a latent image of the pattern. The microstructures in resist polymer can be then revealed using a chemical developer that removes exposed resist, while leaving unexposed resist unaffected. In our system the size of the rectangular beam spot is programmably defined by two L-shaped tantalum blades with well-polished edges. This allows rapid exposure of entire rectangular pattern elements up to 500 × 500 μm in one step. By combining different dimensions of the defining aperture with the sample movements relative to the beam spot, entire fluidic patterns with large reservoirs and narrow flow channels can be written over large areas in short time. Fluidic patterns were written in PMMA using 56 MeV14N3+and a 3 MeV4He2+beams from K130 cyclotron and a 1.7 MV Pelletron accelerators, respectively, at the University of Jyväskylä Accelerator Laboratory. The patterns were characterized using SEM, and the factors affecting patterns quality are discussed. © 2008 Elsevier B.V. All rights reserved.